IMPACT OF NITRIC OXIDE SYNTHESIS MODULATORS ON THE CYTOKINES PROFILE IN EXPERIMENTAL ANTIPHOSPHOLIPID SYNDROME - Yaremchuk, O. Z.; Posokhova, K. A.; Kuzmak, I. P.; Kulitska, M. I.; Shevchuk О. О.; Volska, A. S.; Lykhatskyi, P.H. (International Journal of Medicine and Medical Research, 2020)
Background. Antiphospholipid syndrome (APS) is an autoimmune disease characterized by the presence of specific antibodies. Objective. The aim of the study was to investigate the effect of combined use of L-arginine and aminoguanidine on cytokine profile (IL-1β, IL-6, TNF-α, IL-4, IL-10) in experimental APS. Methods. The study was performed on BALB/c female mice. L-arginine (25 mg/kg) and aminoguanidine (10 mg/kg) were used for correction. Serum cytokines concentrations were assessed using an ELISA test. Results. It was found that in APS the concentration of proinflammatory cytokines IL-1β, IL-6 and TNF-a increases in 3.2, 2.3 and 4.5 times respectively, compare to the control. At the same time a decrease of the IL-4 and IL-10 in 1.9 and 2.2 times was evidenced. Aminoguanidine, a selective iNOS inhibitor, caused a significant decrease of TNF-α by 57% (p<0.001), but there were no changes in IL-1β, IL-6, IL-4 and IL-10 compare to the APS-group. L-arginine combined with aminoguanidine caused a significant decrease in the concentration of IL-1β by 30% (p<0.01), IL-6 – by 16% (p<0.05), TNF-a – by 59% (p<0.001) compare to the control. At the same time, the concentration of IL-4 increased by 35% (p <0.01), IL-10 – by 25% (p<0.005). Conclusions. Combined use of the precursor of the NO synthesis L-arginine and aminoguanidine, a selective iNOS inhibitor, leads to a decrease in the concentrations of IL-1β, IL-6, TNF-a and an increase of IL-4 and IL-10 compare to the group of the BALB/c mice with APS and the group of animals administered with aminoguanidine.